Japan : Insurance Core Principles-Detailed Assessment of Observance. (IMF Staff Country Reports; Country Report ;, 2012)
This Working Paper is a detailed assessment of Japan's compliance with the Insurance Core Principles of the International Association of Insurance Supervisors. The paper identifies a reduction in interest rates and equity prices as two factors that influence the structure and functioning of the insurance market and emphasizes the important role played by the Financial Services Agency in supervising and regulating it. As Japan is prone to frequent natural disasters, the insurance sector is of prime importance to its economic and social well-being.